A pomegranate-like high entropy alloy / carbon nano-hybrid material and its preparation method and application
The pomegranate-like high-entropy alloy/carbon nanohybrid materials prepared by the PVA domain-limited carbonization strategy solve the problem of easy agglomeration of high-entropy alloy nanoparticles, improve catalytic activity and stability, and show excellent performance in electrocatalytic nitrogen oxidation.
Patent Information
- Application Number
- CN202310340289.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-03-31
AI Technical Summary
Existing high-entropy alloy nanoparticles are prone to agglomeration during the catalysis process, resulting in a decrease in active sites, low catalytic activity and poor stability.
Through the limited domain carbonization strategy of PVA, carbon nanohybrid materials embedded in ultrafine AuPdPtRhIr high-entropy alloy nanoparticles were prepared to form a pomegranate-like HEA@C nanohybrid structure, effectively inhibiting the agglomeration of nanoparticles.
The active surface area of high-entropy alloy is improved, the exposure of active sites during electrocatalysis is promoted, the effectiveness and stability of the catalyst is significantly improved, and excellent catalytic activity and Faraday efficiency are shown in the field of electrocatalytic nitrogen oxidation.
Smart Images

Figure CN116356369B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of new material preparation and catalysis, and specifically relates to a pomegranate-like high-entropy alloy / carbon nano-hybrid material and a preparation method and application thereof. Background Art
[0002] Nitrogen is widely present in the atmosphere (more than 78% by volume), but due to its chemical inertness, it cannot be directly absorbed and utilized by humans, animals and plants. Therefore, developing a feasible strategy to activate inert nitrogen and convert it into high-value-added products has aroused people's interest.
[0003] Nitrate is one of the most important nitrogen-containing compounds with a wide range of applications in agriculture and industry. Industrial nitric acid is generally produced by the Ostwald process, which is a multi-step catalytic oxidation process of ammonia under extreme conditions (15-25MPa, 400-600°C), accompanied by high energy consumption and excessive emissions of greenhouse gases. Therefore, from the perspective of energy and environmental requirements, it is of great significance to develop a sustainable and economical alternative technology that can achieve the conversion from nitrogen to nitrate. Electrocatalytic nitrogen oxidation reaction provides the possibility of nitrogen fixation under mild conditions of room temperature and atmospheric pressure.
[0004] As one of the most popular new materials, high entropy alloys (HEAs), composed of five or more metal elements in nearly equimolar ratios, have attracted increasing attention due to their unique physical and chemical properties; thanks to their controllable composition, tunable electronic structure, and excellent corrosion and oxidation resistance, HEAs are very suitable for becoming advanced electrocatalysts.
[0005] Since electrochemical reactions usually occur on the surface or interface, nano-scale HEAs particles have a larger specific surface area and more fully exposed active sites compared to bulk materials, which can greatly improve their electrochemical activity. However, the high surface energy of HEAs nanoparticles in the prior art leads to serious agglomeration during the synthesis and electrocatalysis process, which inevitably reduces their effective specific surface area and the number of exposed electrochemical active sites.
[0006] Currently, carbon-based substrates (e.g., carbon black, carbon nanofibers, and graphene) are one of the most commonly used carriers in many thermochemical and electrochemical reactions due to their advantages such as low cost, large specific surface area, and good electrical properties. However, the problem of poor interface stability caused by the weak interface bonding between HEAs and carbon substrates has not been effectively solved; this problem is particularly prominent when the catalyst is operated for a long time or under harsh conditions, resulting in a significant loss of active sites and a serious decline in overall performance.
[0007] Therefore, achieving stable and independent dispersion of HEAs nanoparticles in carbon supports with reasonable nanohybrid structures remains a huge challenge and is also crucial to improving the effectiveness and stability of catalysts. Summary of the invention
[0008] The purpose of the present invention is to solve the problems of low active sites, easy agglomeration, low catalytic activity, poor stability and the like existing in the high entropy alloy materials in the prior art, and to provide a pomegranate-shaped gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nano-hybrid material with simple preparation process, stable structure and excellent electrocatalytic nitrogen oxidation performance.
[0009] The present invention provides a method for preparing a pomegranate-like high entropy alloy / carbon nano-hybrid material. A carbon nano-hybrid material embedded with ultrafine AuPdPtRhIr high entropy alloy nanoparticles is synthesized by a confined carbonization strategy of PVA; the pomegranate-like nano-hybrid structure of HEA@C can effectively inhibit the self-agglomeration of HEA nanoparticles during the electrochemical reaction, thereby maintaining the large specific surface area and highly exposed active site characteristics of the electrode.
[0010] The first object of the present invention is to provide a method for preparing a pomegranate-like gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nano-hybrid material, the method comprising the following steps:
[0011] (1) adding aqueous solutions of potassium chloroaurate (KAuCl4), potassium tetrachloropalladate (K2PdCl4), potassium hexachloroplatinate (K2PtCl6), potassium hexachlororhodiumate (K3RhCl6) and potassium hexachloroiridate (K2IrCl6) to an aqueous solution of polyvinyl alcohol (PVA), stirring uniformly to obtain a mixed solution;
[0012] (2) transferring the mixed solution obtained in step (1) to a hydrothermal kettle for hydrothermal reaction, cooling to room temperature after the reaction, washing the obtained product, and freeze-drying it to obtain a gold-palladium-platinum-rhodium-iridium / polyvinyl alcohol composite material, named AuPdPtRhIr@PVA composite material;
[0013] (3) The AuPdPtRhIr@PVA composite material obtained in step (2) is carbonized under the protection of an inert gas, cooled to room temperature after the treatment, washed and dried to obtain a pomegranate-like gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nanohybrid material, named HEA@C.
[0014] In one embodiment, the concentration of the aqueous solution of KAuCl4, K2PdCl4, K2PtCl6, K3RhCl6 and K2IrCl6 in step (1) is 0.05-0.2 mol / L, and the volume ratio is 1:1:1:1:1; preferably, the concentration of the aqueous solution of KAuCl4, K2PdCl4, K2PtCl6, K3RhCl6 and K2IrCl6 is 0.1 mol / L.
[0015] In one embodiment, the mass concentration of PVA in the PVA aqueous solution in step (1) is 0.5-2%; preferably, the mass concentration of PVA in the PVA aqueous solution is 1%.
[0016] In one embodiment, the hydrothermal reaction conditions in step (2) are: temperature 200-240° C., time 10-14 h. Preferably, the temperature is 220° C., and the time is 12 h.
[0017] In one embodiment, the freeze-drying time in step (2) is 48 to 60 hours.
[0018] In one embodiment, the carbonization treatment in step (3) is carried out at a temperature of 1000-1100°C, for a time of 1-3 hours, and a heating rate of 5°C / min; preferably, the carbonization temperature is 1000°C, and the time is 2 hours.
[0019] In one embodiment, the washing in step (3) is performed using deionized water; the drying temperature is 50-60° C. and the drying time is 10-16 hours; preferably, the drying time is 12 hours.
[0020] The second object of the present invention is to provide a pomegranate-like gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nano-hybrid material (HEA@C) prepared by the above-mentioned method.
[0021] In one embodiment, the pomegranate-like gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nano-hybrid material has a microscopic morphology composed of many microspheres with a narrow particle size distribution, and a large number of independently dispersed ultrafine HEAs nanoparticles are embedded in these spherical particles.
[0022] The third object of the present invention is to provide an application of the above-mentioned pomegranate-shaped gold-palladium-platinum-rhodium-iridium high-entropy alloy / carbon nano-hybrid material in the field of electrocatalytic nitrogen oxidation.
[0023] The fourth object of the present invention is to provide a method for preparing nitrate by electrocatalytic nitrogen oxidation, the method comprising: using an Ag / AgCl electrode, a graphite rod electrode and a carbon paper loaded with the HEA@C catalyst as a reference electrode, a counter electrode and a working electrode, respectively, to form a standard three-electrode system in a K2SO4 electrolyte solution saturated with N2, and reacting the electrode with a current of 10 to 20 mV s-1 Linear scan was performed at a scan rate of ; the preparation was carried out at an applied potential of 1.7-2.1 V vs. RHE.
[0024] Beneficial effects of the present invention:
[0025] The present invention utilizes the confinement effect of PVA to prepare pomegranate-like AuPdPtRhIr high entropy alloy / carbon nano hybrid materials in which AuPdPtRhIr high entropy alloy nanoclusters are uniformly embedded in carbon spheres, thus solving the technical problem that high entropy alloy nanoclusters are easy to agglomerate during the catalytic process, greatly increasing the active surface area of the high entropy alloy, and promoting the exposure of active sites during the electrocatalytic process. In addition, the porous conductive carbon shell derived from PVA not only greatly reduces the resistance between individual HEAs nanoparticles and accelerates the electrochemical reaction kinetics, but also effectively inhibits the self-agglomeration of HEAs nanoparticles during the electrochemical reaction, thereby maintaining the large specific surface area of the electrode and the characteristics of highly exposed active sites, so that the material exhibits excellent catalytic activity and Faraday efficiency in the field of electrocatalytic nitrogen oxidation, with the highest NO3 - The yield was 23.8 μg h -1 mg cat. -1 , the highest Faraday efficiency is 13.8%; in addition, the "cocktail" effect, excellent corrosion resistance and oxidation resistance of HEA in HEA@C material have made outstanding contributions to the electrochemical activity and cycle stability, and have good commercial prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a transmission electron microscope (TEM) image of the AuPdPtRhIr@PVA nanocomposite prepared in Example 1 of the present invention;
[0027] Figure 2 This is an X-ray diffraction (XRD) pattern of the AuPdPtRhIr@PVA nanocomposite material prepared in Example 1 of the present invention;
[0028] Figure 3 TEM images and scanning transmission electron microscopy images of the HEA@C nanohybrid material prepared in Example 1 of the present invention; (a) is a TEM image; (b) and (c) are high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images;
[0029] Figure 4 HAADF-STEM image of the HEA@C nanohybrid material prepared in Example 1 of the present invention and the corresponding energy dispersive X-ray spectroscopy (EDX) element mapping image;
[0030] Figure 5 This is an X-ray diffraction (XRD) pattern of the HEA@C nanohybrid material prepared in Example 1 of the present invention;
[0031] Figure 6 The XRD pattern of the AuPdPtRhIr bulk prepared in Comparative Example 1;
[0032] Figure 7 HAADF-STEM image of the AuPdPtRhIr bulk prepared in Comparative Example 1 and the corresponding EDX element mapping image;
[0033] Figure 8 The yield and Faraday efficiency diagram of the HEA@C nanohybrid material prepared in Example 1 of the present invention when used as a nitrogen oxidation electrocatalyst;
[0034] Fig. 9 This is a graph showing the change in output over time of the HEA@C nanohybrid material prepared in Example 1 of the present invention when used as a nitrogen oxidation electrocatalyst. DETAILED DESCRIPTION
[0035] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0036] Sources of materials involved in the embodiments and comparative examples of the present invention:
[0037] Potassium chloroaurate, potassium tetrachloropalladate, potassium hexachloroplatinate, potassium hexachlororhodiumate, and potassium hexachloroiridate were purchased from Shanghai Jizhi Biochemical Technology Co., Ltd.; polyvinyl alcohol (PVA) was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.
[0038] Example 1
[0039] A method for preparing a pomegranate-like high entropy alloy / carbon nano-hybrid material comprises the following specific preparation steps:
[0040] (1) 0.09 g of PVA was added to 8.91 g of deionized water, and the mixture was stirred to dissolve to obtain a 1 wt% PVA aqueous solution; then, KAuCl4, K2PdCl4, K2PtCl6, K3RhCl6 and K2IrCl6 were respectively dissolved in 1 mL of deionized water to obtain 0.1 mol / L KAuCl4, K2PdCl4, K2PtCl6, K3RhCl6 and K2IrCl6 aqueous solutions; and the five metal salt solutions were mixed and stirred with the PVA aqueous solution to form a mixed solution;
[0041] (2) The mixed solution was transferred to a 20 mL hydrothermal reactor and hydrothermaled at 220 °C for 12 h. After cooling to room temperature, the obtained product was washed with deionized water for 3 times and freeze-dried for 48 h to obtain AuPdPtRhIr@PVA composite material.
[0042] (3) The obtained AuPdPtRhIr@PVA composite material was carbonized at 1000°C for 2 h under argon protection with a heating rate of 5°C / min; after cooling to room temperature, it was washed and dried at 60°C for 12 h to obtain a pomegranate-shaped HEA@C nanohybrid material.
[0043] Comparative Example 1
[0044] Referring to Example 1, the only difference is that the mass of PVA in Example 1 is changed to 0 g, and the other conditions and parameters are the same as those in Example 1. The obtained composite material is recorded as AuPdPtRhIr bulk.
[0045] Performance measurement
[0046] 1. X-ray diffractometer (XRD) and transmission electron microscope (TEM) were used to characterize the morphology and composition of the AuPdPtRhIr@PVA composite material, HEA@C nanohybrid material and AuPdPtRhIr bulk material prepared in Example 1. The results are as follows:
[0047] turn out:
[0048] (1) TEM test results show that: Figure 1 As shown, the AuPdPtRhIr@PVA composite material prepared in Example 1 exhibits a pomegranate-like structure, that is, a large number of ultrafine metal nanoparticles are embedded in the spherical PVA microspheres, and there is no obvious metal agglomeration phenomenon.
[0049] (2) XRD test results show that: Figure 2 As shown, the characteristic peaks of metal Au (JSPDS#-04-0784) at 2θ=38.4°, 44.5°, 64.7° and 77.6° can be clearly observed in the XRD pattern of the AuPdPtRhIr@PVA composite material prepared in Example 1. In addition, the peaks at 2θ=40.0°, 46.6°, 68.1°, 81.8° and 86.4° further indicate that a single-phase alloy with a face-centered cubic (FCC) structure is formed in the AuPdPtRhIr@PVA composite material.
[0050] (3) TEM test results show that: Figure 3 As shown, the HEA@C nanohybrid material prepared in Example 1 is composed of many microspheres with a narrow particle size distribution ( Figure 3a), These spherical particles are interconnected to form a 3D framework with efficient ion / electron transport pathways.
[0051] In addition, the HAADF-STEM images of the HEA@C nanohybrids showed that a large number of HEA nanoparticles were embedded in the PVA-derived carbon spheres ( Figure 3 b); A large number of ultrafine HEA nanoparticles (~5nm) are independently dispersed in the carbon matrix without obvious agglomeration ( Figure 3 c), which is mainly attributed to the confinement effect of PVA during the carbonization process.
[0052] (4) The results of HAADF-STEM and the corresponding energy dispersive X-ray spectroscopy (EDX) element mapping tests show that: Figure 4 As shown, various metal elements (Au, Pd, Pt, Rh and Ir) in the HEA@C nanohybrid material prepared in Example 1 are randomly and uniformly distributed in each nanoparticle, proving that a single-phase solid solution alloy is formed in the HEA@C nanohybrid.
[0053] (5) XRD test results show that: Figure 5 As shown, the XRD pattern of the HEA@C nanohybrid material prepared in Example 1 shows a characteristic diffraction peak at 2θ=~26.0° corresponding to the (002) plane of graphite carbon. It should be noted that the diffraction peak of the single-phase FCC structure is still well maintained, while the characteristic diffraction peak of metal Au completely disappears, indicating that a single-phase solid solution HEA with an FCC structure is finally formed after the pyrolysis process.
[0054] (6) XRD test results show that: Figure 6 As shown, the XRD pattern of the AuPdPtRhIr bulk material prepared in Comparative Example 1 shows that the characteristic diffraction peak of the Au phase completely disappears, and only two groups of diffraction peaks belonging to the FCC structure alloy can be observed, indicating that a single-phase FCC structured high-entropy alloy cannot be formed without the confinement effect of PVA.
[0055] (7) The results of HAADF-STEM and the corresponding energy dispersive X-ray spectroscopy (EDX) element mapping tests show that: Figure 7 As shown, the EDX element mapping of the AuPdPtRhIr bulk material prepared in Comparative Example 1 shows that the Au, Pd, Pt, Rh and Ir elements in the AuPdPtRhIr bulk are unevenly distributed, indicating that the preparation of the single-phase solid solution HEA has failed, further illustrating that the absence of PVA plays a vital role in the preparation of the single-phase HEA.
[0056] 2. Electrochemical performance measurement of the HEA@C nanohybrid material prepared in Example 1
[0057] The electrochemical activity of HEA@C nanohybrid materials for nitrogen oxidation reaction (NOR) was tested in 0.1 mol / L K2SO4 solution using a standard three-electrode system. Ag / AgCl electrode, graphite rod electrode and carbon paper loaded with catalyst were used as reference electrode, counter electrode and working electrode, respectively. Before NOR test, N2 was passed through the electrolyte for 30 min to saturate the electrolyte with N2; all potentials mentioned are for reversible hydrogen electrode (RHE) without additional statement.
[0058] The working electrode was prepared by dispersing 5 mg of catalyst and 25 μL of 5% Nafion solution in 5 mL of ethanol and ultrasonicating for 1 h to obtain a uniform ink. Then, 0.3 mL of catalyst ink (containing 300 μg of HEA@C catalyst) was sprayed onto a 1×1 cm 2 The working electrode was obtained by placing the carbon paper on the surface of the carbon paper. The working electrode was charged at 10 mV s -1 The polarization curves were subjected to linear sweep voltammetry (LSV) at a scan rate of 1.7 V vs. RHE for 2 h to evaluate the electrocatalytic performance of the HEA@C catalyst.
[0059] Product NO3 - Determination: Take out 2mL of electrolyte from the electrolytic cell and dilute to 5mL, then add 0.1mL of 1mol / LHCl and 0.01mL of 0.8wt% aminosulfonic acid solution to the above solution; use a UV-visible spectrophotometer to test the absorption spectrum and record the absorption intensity at wavelengths of 220 and 275nm. The final absorbance value is calculated by the following equation:
[0060] A=A 220nm –2A 275nm
[0061] A series of standard potassium nitrate solutions were used to calibrate the concentration-absorbance curve. The potassium nitrate crystals were dried at 105-110°C for 2 hours.
[0062] The electrochemical workstation test results show that: Figure 8 As shown in Figure 1, the HEA@C nanohybrid material prepared in Example 1 exhibited excellent electrochemical activity as a nitrogen oxidation electrocatalyst, i.e., 23.8 μg h - 1 mg cat. -1 Maximum NO3 - The highest Faradaic efficiency of 13.8% was achieved at 1.7 V vs. RHE.
[0063] In order to evaluate the sustained electrocatalytic synthesis of NO3 - The ability of NO3 - Output, such as Fig. 9 As shown. NO3 - The total yield was from 2 hours (0.04 mg mg cat -1 ) to 20 hours (0.41mgmg cat -1 ) increases almost linearly, demonstrating the excellent electrochemical stability of the HEA@C nanohybrid material during the NOR process.
Claims
1. A method for preparing a pomegranate-like high entropy alloy / carbon nano-hybrid material, characterized in that: The method comprises the following steps: (1) adding aqueous solutions of potassium chloroaurate, potassium tetrachloropalladate, potassium hexachloroplatinate, potassium hexachlororhodiumate and potassium hexachloroiridate to an aqueous solution of polyvinyl alcohol, stirring evenly to obtain a mixed solution; (2) transferring the mixed solution obtained in step (1) to a hydrothermal reactor for hydrothermal reaction, cooling to room temperature after the reaction, washing the obtained product, and freeze-drying it to obtain a gold-palladium-platinum-rhodium-iridium / polyvinyl alcohol composite material, named AuPdPtRhIr@PVA composite material; the hydrothermal reaction conditions are: temperature 200-240°C, time 10-14 h; (3) The AuPdPtRhIr@PVA composite material obtained in step (2) is carbonized under inert gas protection, cooled to room temperature, washed and dried to obtain a pomegranate-like gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nanohybrid material, named HEA@C; The carbonization treatment is carried out at a temperature of 1000-1100°C, for a time of 1-3 h, and at a heating rate of 5°C / min.
2. The method according to claim 1, characterized in that The concentration of the aqueous solution of potassium chloroaurate, potassium tetrachloropalladate, potassium hexachloroplatinate, potassium hexachlororhodiumate and potassium hexachloroiridate in step (1) is 0.05-0.2 mol / L, and the volume ratio is 1:1:1:1:
1.
3. The method according to claim 1, characterized in that The mass concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution in step (1) is 0.5-2%.
4. The method according to claim 1, characterized in that The freeze-drying time in step (2) is 48 to 60 hours.
5. The method according to claim 1, characterized in that The washing in step (3) is performed using deionized water; the drying temperature is 50-60°C and the drying time is 10-16 h.
6. A pomegranate-like gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nano-hybrid material HEA@C prepared by the method described in any one of claims 1 to 5.
7. Use of the pomegranate-like gold-palladium-platinum-rhodium-iridium high entropy alloy / carbon nano-hybrid material HEA@C as described in claim 6 in the field of electrocatalytic nitrogen oxidation.
8. A method for preparing nitrates by electrocatalytic nitrogen oxidation, characterized in that: The method comprises: using an Ag / AgCl electrode, a graphite rod electrode and a carbon paper loaded with the HEA@C catalyst according to claim 6 as a reference electrode, a counter electrode and a working electrode respectively, constructing a standard three-electrode system in a K2SO4 electrolyte solution saturated with N2, and conducting a 10-20 mV s -1 Linear scan was performed at a scan rate of 1.7-2.1 V vs. RHE; the preparation was carried out at an applied potential of 1.7-2.1 V vs. RHE.